Neurological outcomes 1 year after COVID‐19 diagnosis: A prospective longitudinal cohort study. (23rd March 2022) - Rass, Verena; Beer, Ronny; Schiefecker, Alois Josef; Lindner, Anna; Kofler, Mario; Ianosi, Bogdan Andrei; Mahlknecht, Philipp; Heim, Beatrice; Peball, Marina; Carbone, Federico; Limmert, Victoria; Kindl, Philipp; et al.
Abstract: Background and purpose: Neurological sequelae from coronavirus disease 2019 (COVID‐19) may persist after recovery from acute infection. Here, the aim was to describe the natural history of neurological manifestations over 1 year after COVID‐19. Methods: A prospective, multicentre, longitudinal cohort study in COVID‐19 survivors was performed. At a 3‐month and 1‐year follow‐up, patients were assessed for neurological impairments by a neurological examination and a standardized test battery including the assessment of hyposmia (16‐item Sniffin' Sticks test), cognitive deficits (Montreal Cognitive Assessment < 26) and mental health (Hospital Anxiety and Depression Scale and Post‐traumatic Stress Disorder Checklist 5). Results: Eighty‐one patients were evaluated 1 year after COVID‐19, out of which 76 (94%) patients completed a 3‐month and 1‐year follow‐up. Patients were 54 (47–64) years old and 59% were male. New and persistent neurological disorders were found in 15% (3 months) and 12% (10/81; 1 year). Symptoms at 1‐year follow‐up were reported by 48/81 (59%) patients, including fatigue (38%), concentration difficulties (25%), forgetfulness (25%), sleep disturbances (22%), myalgia (17%), limb weakness (17%), headache (16%), impaired sensation (16%) and hyposmia (15%). Neurological examination revealed findings in 52/81 (64%) patients without improvement over time (3 months, 61%, p = 0.230) including objective hyposmia (Sniffin' Sticks test <13; 51%). Cognitive deficits were apparent in 18%, whereas signs of depression, anxiety and post‐traumatic stress disorders were found in 6%, 29% and 10% respectively 1 year after infection. These mental and cognitive disorders had not improved after the 3‐month follow‐up (all p > 0.05). Conclusion: Our data indicate that a significant patient number still suffer from neurological sequelae including neuropsychiatric symptoms 1 year after COVID‐19 calling for interdisciplinary management of these patients. Abstract : Out of 81 patients, 48 (59%) reported persistent symptoms that were not evident before COVID‐19 at the 1‐year follow‐up. New and persistent neurological disorders were found in 15% (3 months) and 12% (10/81; 1‐year). Cognitive deficits one year after COVID‐19 were apparent in 18%, whereas depression, anxiety, and post‐traumatic stress disorders were found in 6%, 29%, and 10% one year after infection, respectively. Our data indicate that a significant patient number still suffer from neurological sequelae including neuropsychiatric symptoms one year after COVID‐19.